Home Health Care Nurses' Challenges in Implementing Person-Centered Care among Elderly Patients with Dementia - Agga, Abdulkarim Omar; Sattar, Nada; Macaraeg, Veronica Cristina Brillantes (Nurse Media Journal of Nursing, 2025)
Background: As the global need to address the care of elderly patients with dementia continues to rise, various health care systems have adopted different approaches to uphold the highest form of dignity, respect, autonomy, and preferences of their patients. One such approach is Person-Centered Care (PCC), which has shown benefits in improving the quality of life for elderly patients with dementia and their caregivers. However, despite its recognized benefits, PCC faces implementation challenges and is not widely adopted in some health care settings, as its effectiveness in challenging scenarios remains unclear. Additionally, limited research exists focusing on the experiences and challenges encountered by home health care nurses in these cases.Purpose: The primary aim of this study was to identify and describe the challenges faced by home health care nurses in implementing PCC, specifically for elderly patients with dementia. Methods: The study utilized Husserl’s transcendental phenomenology method. The participants included home health care nurses currently working with patients who had been medically diagnosed with dementia for at least six months. Sixteen participants were selected through purposive sampling. The nurses underwent thorough face-to-face interviews with the researchers. Inductive thematic analysis by Braun and Clarke was used to pragmatically organize the lived experiences. Results: Upon data interpretation, the study revealed two major themes, namely:  personal challenges with two sub-themes, (1) communication barriers and (2) limited training; and external challenges with two sub-themes; (1) powerlessness in decision making and (2) uncooperative patients.Conclusion: The study highlights the various challenges faced by home health care nurses in implementing PCC for elderly patients with dementia. To improve nurses’ capability to manage these challenges, support through education and training, policy development, and stakeholder involvement is essential to enhance the care delivery process.